ANALYSIS OF PROBLEMS AND SOLUTIONS OF HALAL INDUSTRY IN EAST JAVA (Ar Rehla: Journal of Islamic Tourism Halal Food Islamic Traveling and Creative Economy, 2025)
Abstract: The halal industry trend continues to grow because it is influenced by the increasing population of Muslim communities with increasing income as well as increasing economic growth. East Java has enormous potential as a center for developing the halal industry. However, there are quite big challenges because there is no master plan for developing the halal industry, halal certification is not yet optimal with many halal products, there is no infrastructure available, limited educational, training and research facilities related to industry, halal logistics and halal industrial areas and a lack of professional and competent human resources. Using the Analytical Network Process (ANP) method. Finding priority problems where generally halal industry human resources, namely MSME players, still have a narrow mindset; MSME players still lack knowledge regarding halal certification of their products. Meanwhile, the priority finding of the solution is to improve the qualifications of MSME human resources using technology to meet halal product standards and product diversification. The next strategic priority finding is the strategy for strengthening micro, small and medium enterprises (MSMEs) as the main driver of halal values.Keywords: problems; solutions; halal industry; east java. Abstrak: Tren industri halal yang terus berkembang karena dipengaruhi peningkatan populasi masyarakat muslim kelas menengah, juga dengan meningkatnya pendapatan masyarakat, mendorong meningkatnya pertumbuhan ekonomi.  Jawa Timur dengan  potensi sangat besar sebagai pusat pengembangan industri halal, namun menghadapi tantangan cukup besar  karena belum adanya masterplan dalam pengembangan industri halal, dengan kondisi belum optimalnya sertifikasi halal pada produk-produk industry. Di sisi lain dengan keterbatasan sarana pendidikan, pelatihan dan penelitian berkaitan industri, logistik halal dan mengoptimalkan kawasan industri halal serta sedikitnya SDM profesional yang kompeten menjadi tantangan dalam pengembangan industry halal.. Dengan metode Analityc Network Process (ANP), menemukan prioritas masalah di mana umumnya SDM industry halal yaitu Para pelaku UMKM masih  pola pikir sempit; Para pelaku UMKM masih kurang pengetahuan berkaitan sertifikasi halal produk-produknya. Sementara temuan prioritas solusi adalah  meningkatkan kualifikasi SDM UMKM penggunaan tekhnologi dalam memenuhi standar produk halal dan diversifikasi produk. Selanjutnya temuan prioritas strategi adalah Strategi penguatan usaha mikro, kecil dan menengah (UMKM) sebagai penggerak utama nilai halal.Kata Kunci: masalah; solusi;  industri halal; jawa timur.
Keywords: problems; solutions; halal industry; east java